Postparturient liver diseases of dairy cattle (Ketosis, fatty liver). II. Management principles - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two of the commonest in practice postparturient liver diseases of dairy cows, ketosis and fatty liver, are discussed in this paper. It is not uncommon for both diseases to occur simultaneously, or each to act as a predisposing factor for the other. Clinical findings are nonspecific and certain biochemical parameters can be used as diagnostic tools. Treatment is focused in restoring glucose and energy balance of the affected animals with the administration of glucose, glucogenic substances, corticosteroids, insulin and lipotropic agents. Prevention aims in proper herd management, especially in terms of feeding rations.